A review of the state-of-the-art distributed compressive video sensing architectures. (1st January 2014) - Imran, Noreen; Seet, Boon-Chong; Fong, A.C.M.
Low complexity video coding that provides efficient compression with reasonable reconstruction quality has been a desired requirement for resource-constrained video sensors in distributed vision-based sensing applications. In this paper, we present a review of the state-of-the-art codec architectures based on distributed compressive video sensing (DCVS), which is a relatively new video coding paradigm that integrates the techniques of distributed video coding (DVC) and compressive sensing (CS). The review includes a comparative discussion of several well-known DCVS architectures in literature with a focus on their functional aspects, and suggests a number of possible enhancements to the design of these architectures.